Pemetaan Kinerja Finansial Pt Hutama Karya (Persero) Periode 2023–2025 - Rayan Akhsan Ramadhan; Iyan Ramadhan Putra; Muhammad Faiz; Rifan Ardiansyah; Arif Rakhman (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to examine the financial condition of PT Hutama Karya (Persero) over a three-year period, from 2023 to 2025, using a financial ratio analysis approach. The research employed a quantitative descriptive method utilizing secondary data in the form of independently audited consolidated financial statements. The analysis covered four dimensions of financial ratios: liquidity (current ratio and quick ratio), solvency (debt-to-equity ratio, debt-to-assets ratio, equity ratio, and interest coverage ratio), profitability (gross profit margin, operating profit margin, net profit margin, return on assets, and return on equity), and activity (total asset turnover). The results indicate that liquidity experienced pressure in 2025, as reflected by a decline in the current ratio to 1.71 times, mainly due to reduced cash balances resulting from the accelerated completion of the Trans-Sumatra Toll Road project. On the other hand, the company’s capital structure continued to improve, as evidenced by a decrease in the debt-to-equity ratio from 0.46 times to 0.34 times. Profitability also demonstrated consistent growth, with the net profit margin increasing from 6.95% in 2023 to 12.29% in 2025. These findings suggest that although short-term liquidity management still requires attention, the overall financial performance of PT Hutama Karya (Persero) has been on a steadily improving trajectory.